Parent-mediated intervention versus no intervention for infants at high risk of autism: a parallel, single-blind, randomised trial. (February 2015) - Green, Jonathan; Charman, Tony; Pickles, Andrew; Wan, Ming W; Elsabbagh, Mayada; Slonims, Vicky; Taylor, Carol; McNally, Janet; Booth, Rhonda; Gliga, Teodora; Jones, Emily J H; Harrop, Clare; et al.
Summary: Background: Risk markers for later autism identified in the first year of life present plausible intervention targets during early development. We aimed to assess the effect of a parent-mediated intervention for infants at high risk of autism on these markers. Methods: We did a two-site, two-arm assessor-blinded randomised controlled trial of families with an infant at familial high risk of autism aged 7–10 months, testing the adapted Video Interaction to Promote Positive Parenting (iBASIS-VIPP) versus no intervention. Families were randomly assigned to intervention or no intervention groups using a permuted block approach stratified by centre. Assessors, but not families or therapists, were masked to group assignment. The primary outcome was infant attentiveness to parent. Regression analysis was done on an intention-to-treat basis. This trial is registered with ISCRTN Registry, number ISRCTN87373263. Findings: We randomly assigned 54 families between April 11, 2011, and Dec 4, 2012 (28 to intervention, 26 to no intervention). Although CIs sometimes include the null, point estimates suggest that the intervention increased the primary outcome of infant attentiveness to parent (effect size 0·29, 95% CI −0·26 to 0·86, thus including possibilities ranging from a small negative treatment effect to a strongly positive treatment effect). For secondary outcomes, the intervention reduced autism-risk behaviours (0·50, CI −0·15 to 1·08), increased parental non-directiveness (0·81, 0·28 to 1·52), improved attention disengagement (0·48, −0·01 to 1·02), and improved parent-rated infant adaptive function (χ 2 [2] 15·39, p=0·0005). There was a possibility of nil or negative effect in language and responsivity to vowel change (P1: ES–0·62, CI −2·42 to 0·31; P2: −0·29, −1·55 to 0·71). Interpretation: With the exception of the response to vowel change, our study showed positive estimates across a wide range of behavioural and brain function risk-markers and developmental outcomes that are consistent with a moderate intervention effect to reduce the risk for later autism. However, the estimates have wide CIs that include possible nil or small negative effects. The results are encouraging for development and prevention science, but need larger-scale replication to improve precision. Funding: Autistica, Waterloo Foundation, Autism Speaks, and the UK Medical Research Council.